THE SYNTHESIS OF MYTH AND HISTORY IN POSTCOLONIAL WRITING: THE POETICS OF TONI MORRISON'S “BELOVED” - Rakhimova Marguba Khamzayevna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines magical realism as a narrative method that combines the supernatural with a detailly crafted reality. Originating in art criticism and popularised in Latin American literature, it challenges Western rationalism. The analysis focuses on its role in English-language postcolonial contexts, particularly in the work of Toni Morrison. Morrison revives lost tales and reimagines the anguish of slavery in books like Beloved by utilizing magical elements derived from African American tradition. She used magical realism, which goes beyond a mere literary device to become an act of historical justice, to restore marginalized voices and shape cultural memory by supporting the cultural truth of these myths.